REFERRAL PATTERN AND SATISFACTION LEVEL OF PATIENTS WITH MUSCULOSKELETAL DISORDERS TOWARDS PHYSIOTHERAPY - Fatimah, Ishrat; Khattak, Saadia; Sultan, Mahwish; Ibrahim, Momina; Noor, Ayesha (Annals of Allied Health Sciences, 2019)
OBJECTIVE: The objective of this study was to determine referral pattern and satisfaction level of patients with musculoskeletal disorders towards physiotherapy. METHODS: Cross sectional study with a consecutive series of participants was conducted in Peshawar, Pakistan in 2017. Data was collected from 300 participants who visited physiotherapy departments with musculoskeletal complaints. A Structured Questionnaire comprised of questions related to demographic information, referral mode and satisfaction with physiotherapy was used for data collection. RESULTS: The Percentage of participants that were referred to physiotherapy for the treatment was 64% while 36% of them availed direct access to physical therapy. Most of participantsi.e. 50% were referred by Orthopedics. Most of the musculoskeletal disorder cases were back pain i.e. 38% followed by shoulder pain i.e. 19.7%. Regarding satisfaction level 83% of the participants were satisfied from physiotherapy. CONCLUSION: This study concluded that most of the participants are referred for physiotherapy instead of direct access. Orthopedics and general physicians played an important role in referral of the patients to physical therapy. This study showed that there was great cooperation of specialist in referral and sufficient awareness of physical therapy among participants which led to high level of satisfaction.